Influência da aeração artificial do tempo de cheia em um sistema wetland construído tidal flow - Pedro, Beatriz Larissa (2023)
Constructed wetlands are seen as an alternative in decentralized wastewater treatment, presenting a high efficiency in the removal of pollutants. These systems are characterized by low implementation and maintenance costs, and a simple and sustainable operation. Different modes of operation can bring even more satisfactory results for the removal of pollutants. The objective of the present work was to evaluate the influence of different flooding times and the application of artificial aeration on the effluent in a constructed wetland with tidal flow operation. The system (volume of 117 L) treated synthetic wastewater of low concentration, with red ceramic fragments as substrate and Alternanthera philoxeroides as macrophyte. The effluent was fed in a descending manner with subsurface flow. The operation of the system consisted in applying three distinct flood times in three different phases (48, 24 and 12h), followed by artificial aeration of the effluent in an external tank for 3hours (during this period the WC remains empty), then the effluent returns to the system (recirculation) and remains for another 9hours, in the sequence occurs the discharge of the effluent and a new cycle begins. The maximum efficiencies of COD removal were 94%, 93% and 94% for phases 1, 2 and 3, respectively, where no significant differences were found among the phases. For the removal of phosphorous matter (PT) phase 3 presented lower removal efficiency (79%), while phases 1 and 2 had values of 87% and 86%, respectively, and in all phases the maximum efficiencies were observed after artificial aeration and recirculation. The nitrogenous matter presented satisfactory removal results for NTK and N-Amon mainly in phases 1 and 2, with removal efficiencies of 81% and 78% for NTK and 98% and 95% for N-Amon. In phase 3, NTK had a lower removal efficiency (53%). In all phases, there was no significant change in nitrate (N-NO3-). Nitrite (N-NO2-) showed significant increase in the final effluent of phase 1 (540%). Therefore, it is possible to realize that for phosphorous matter, the flooding time and the insertion of aeration in the effluent helped in the removal of PT. For nitrogenous matter, the nitrification process was favored in phase 1, where the flooding time was longer (48h), increasing the nitrite concentration (after the increase of dissolved oxygen in the effluent) and promoting a higher removal efficiency of N-Amon and NTK.